TEACHER’S DIRECTIVE ILLOCUTIONARY ACTS IN ENGLISH LANGUAGE CLASSROOM - Erani Putri Chaniago; Heri Kuswoyo (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
The proficiency of the teacher is an important thing to achieve the goal of studying in class. Teachers can use many utterances such as commanding, requesting and also suggesting to students to control the class while teaching and learning progress is going on. Directing an utterance to students should be done rightly to make the messages of utterances conveyed to the students in the class.This research was conducted to find out the types and how the way teacher used directive illocutionary acts in English language classrooms at a course in Bandar Lampung. This research also explains the context of meaning inside of the utterance that was spoken by the teacher in the class while delivering the material. In addition, the qualitative method was applied in this research.In particular, seventeen utterances are categorized as command type of directive illocutionary act, with 73,92% of it. Meanwhile, four utterances are categorized as request type of directive illocutionary acts with 17,39% of it. The last type of directive illocutionary act is request and the writer found two utterances with 8,69% of it.Keywords: Directive Illocutionary Acts, English Language Classroom, English Course, Teacher